Gender Difference in The Prevalence of Financial Stress, Anxiety and Depression Among South-East Nigerian University Students - Nweke, Peter; Eneogu, Njideka Dorathy; Amedu, Amos Nnaemeka (Soedirman Economics Education Journal, 2025)
Gender has been identified as a predictor of mental health (stress, anxiety, depression) among university students. This study determined gender influence on the prevalence of financial stress, anxiety, and depression among undergraduate students studying Economics education in South-East public universities. The study employed ex post facto design. The population studied was 1,116 Economics education undergraduate students. The sample consisted of 294 respondents, which was gotten using Yamene’s (1967) sample size determination formula and selected using a multi-stage sampling technique. The study was guided by 3 research questions and 3 hypotheses. Financial Stress, Anxiety, and Depression Scale (FSADS) was used in gathering data. The reliability estimate of the instrument was 0.96 gotten using Cronbach Alpha. Research questions and hypotheses were tested using mean and t-tests at 0.05 level of significance respectively. The finding showed that students’ gender did not influence the prevalence of financial stress, anxiety, and depression among Economics education undergraduate students. It was recommended among other things that; improvement in the fund given to the students by their sponsors should be for all students because the financial challenges faced by the students are not gender-based.